Biosorption of diazinon by a pre-treated alimentary industrial waste: equilibrium and kinetic modeling - N. Yeddou Mezenner; H. Lagha; H. Kais; M. Trari (Applied Water Science, 2017)
Abstract This study explores the feasibility of pre-treated coffee waste (PCW) as biosorbent for the removal of diazinon. The effect of the pesticide concentration (6–20 mg L−1), contact time, adsorbent dose (0.2–1.2 g L−1), solution pH (3–11.5), temperature (15–40 °C) and co-existing inorganic ions (H2PO4 −, NO3 −) on the diazinon biosorption over PCW is investigated. The experimental results indicate an optimal pH of 7.3 for the diazinon elimination on PCW (1 g L−1). The Langmuir model describes well the isotherm data with a high regression coefficient (R 2 > 0.990) and a maximum monolayer biosorption capacity of 18.52 mg g−1 at 15 °C. It is also observed that the intra-particle diffusion is not the rate-controlling step. A comparison is evaluated between the pseudo-second-order and intra-particle diffusion kinetic models; the experimental data are well fitted by the pseudo-second-order kinetic model. The biosorption capacity decreases with increasing temperature for a diazinon concentration of 10 mg L−1. The negative enthalpy ΔH° (−63.57 kJ/mol) indicates that the diazinon biosorption onto PCW is exothermic. Under optimal conditions, the biosorption reaches 95% after 90 min. The removal efficiency decreases from 95 to 65.67 and 48.9% for the diazinon alone and in the presence of NO3 − and H2PO4 − (100 mg L−1), respectively.